Internacionalização de empresas multinacionais: a dinâmica dos investimentos sequenciais - Battistuzzo, Flávio Jorge Freire D'Andrade (2020)
One of the main aspects studied in International Business (IB) refers to the way in which an organization is internationalized. The theories of development of the multinational enterprise (MNE), with an economic focus, are characterized by a model of investment decisions without considering the experience and knowledge acquired by MNE through the realization of Sequential Foreign Direct Investments (SFDI). This thesis seeks to fill a gap in IB theory, when considering the dynamics of SFDI in the internationalization of organizations. The objectives of this thesis are: (i) to evaluate the existing knowledge about SFDI (ii) to evaluate the relationship between sequential investments and the survival of subsidiaries considering the institutional elements and (iii) to evaluate the relationship between sequential investments and the performance of foreign subsidiaries considering the learning gained from the expansion of MNEs. The systematic analysis allowed the development of a framework relating sequential investments and institutional environment, path dependency, learning and location. The survival of the subsidiaries was assessed, and the results indicate that the country's situation in terms of economic development and the region where they operate still play a relevant role in the survival of the subsidiaries. In terms of sequential investments in the country, region and the world, there is no significant impact on the survival rate of subsidiaries. Regarding distances, the cultural-cognitive distance was significant in the survival of subsidiaries. In analyzing the relationship between ISDE and the subsidiary's performance, the research showed that its performance is positively related to the experience obtained with the sequential investments made in the country, region and world, for countries with higher Gross Domestic Product (GDP). Operating experience (local) positively affects the performance of subsidiaries in countries with higher GDPs. This study contributes to the academy by highlighting the importance of sequential investments in different contexts (local, regional and worldwide) and by relating sequential investments to learning, institutional distance and subsidiary survival in an assessment over a 75-year period.